A Game Theory Approach for Efficient Node Clustering Based on Unstable Ranging Transmission in MANET - Preethi Author, R; R. Anbuselvi Author, Dr (International Journal of Engineering and Technology, 2018)
In Mobile Ad Hoc Network (MANET), improving scalability, energy efficiency and network lifetime are the most important and challenging issues. Node Clustering is a well known solution for handling these issues. While existing work focused on stable transmission range, this paper uses unstable ranges transmission for clustering nodes in network. Game theory has been used in fields of science such as economics and biology, but recently it was used in MANET for clustering problem. Grouping mobile nodes into convenient clusters can reduce routing overhead and provide more scalable solution. The main objective of this work is to clustering of nodes in MANET and selects energy efficient cluster head to improve the network lifetime using game theoretical model. This paper proposes an efficient algorithm for Node Clustering based on Unstable Ranging Transmission (NCURT). In addition to this, a game theory based cluster head (CH) selection algorithm is proposed to selects CH based on Evolutionary game theory approach where each node behaves selfish or unselfish based on the strategy selection. Analytical and simulation studies are carried out to assess the performance of the proposed cluster formation and cluster head selection algorithm. The numerical results verify that the proposed approach is effective and efficient to guarantee life time and energy efficiency in MANET.Â Â